Cytological differentiation between benign and malignant perianal gland proliferative lesions in dogs: a preliminary study. (1st August 2019) - Sabattini, S.; Renzi, A.; Rigillo, A.; Scarpa, F.; Capitani, O.; Tinto, D.; Brenda, A.; Bettini, G.
Abstract : Objectives: To evaluate the diagnostic utility of individual cytological criteria and their best combination to differentiate benign from malignant perianal gland proliferative lesions in dogs. Materials and Methods: Retrospective study of cytological samples of canine perianal gland proliferative lesions that had subsequent histopathological confirmation. Results: Seventy‐seven perianal gland nodules from 56 dogs were included. Histologically, lesions were diagnosed as hyperplasia (n=2), adenoma (n=53), epithelioma (n=6) and carcinoma (n=16). Of the 28 cytological criteria assessed, 13 showed promise for distinguishing benign from malignant lesions. A diagnostic algorithm with an 87% accuracy (sensitivity, 90.9%; specificity, 85.4%) was developed from these data. Clinical Significance: Cytological evaluation can provide useful information for presurgical differentiation between benign and malignant hepatoid gland proliferative lesions. The proposed algorithm must be validated and tested for reproducibility in further, preferably larger, series of cases.